Expression of galectin in patients with psoriasis vulgaris - Qing CHENG; Xiao-hua WANG; Bin YANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2020)
Objective: To investigate the expression of galectin (Gal) in psoriasis vulgaris. Methods: The serum levels of Gal-1, Gal-3, Gal-7 and Gal-9 were measured using ELISA, in 30 patients with psoriasis vulgaris (PV) and 30 normal controls. Immunohistochemistry was used to compare expression and cellular localization of cutaneous Gal-1, Gal-3, Gal-7, Gal-9 between 15 psoriatic lesions and 10 normal controls. Results: In comparison to normal controls, serum levels of Gal-1 was significantly elevated in psoriatic patients [(39.57±11.33) ng/mL vs (31.93±7.98) ng/mL, t=3.02, P=0.004], and positively correlated with PASI score (r=0.37, P=0.049). In the dermis, expression levels of Gal-1 in psoriatic patients was higher than that in normal controls (0.030±0.043 vs 0.011±0.002, t=3.34, P=0.003). In the epidermis, psoriatic lesions exhibited higher expression levels of Gal-7 (0.090±0.011 vs 0.049±0.009, t=2.58, P<=0.017), and lower levels of both Gal-3 (0.016±0.001 vs 0.060±0.018, t=-2.85, P<=0.009) and Gal-9 (0.011±0.002 vs 0.049±0.007, t=-6.16, P<0.001) compared to normal controls. Conclusion: Differential expression levels and cellular distribution of Gal-1, Gal-3, Gal-7, Gal-9 in both serum and the skin suggest their distinct role in the pathogenesis of psoriasis.